2014
DOI: 10.1007/s11701-014-0489-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of robotic telerounding in the surgical intensive care units impact on medical education

Abstract: Robotic telerounding is effective from the standpoint of patients' satisfaction and patients' care in teaching and community hospitals. However, the impact of robotic telerounding by the intensivist rounding remotely in the surgical intensive care unit (SICU), on patients' outcome and on the education of medical students physician assistants and surgical residents, as well as on nurses' satisfaction has not been studied. Prospective evaluation of robotic telerounding (RT) using a Likert Scale measuring tool to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Multiple studies in a variety of ICUs have demonstrated high acceptability of both medical and nursing staff with regard to remote presence technology 68 , 69. Our findings demonstrate a similarly positive staff response on general surgical wards.…”
Section: Discussionsupporting
confidence: 67%
“…Multiple studies in a variety of ICUs have demonstrated high acceptability of both medical and nursing staff with regard to remote presence technology 68 , 69. Our findings demonstrate a similarly positive staff response on general surgical wards.…”
Section: Discussionsupporting
confidence: 67%
“…Also in the near future, nursing robotics with an artificial intelligence (AI) function may be applied in clinical settings (Erikson & Salzmann-Erikson, 2016). However, nurses tend to believe that robots have drawbacks and that the physical presence of a nurse greatly helps patients (Bettinelli, Lei, Beane, Mackey, & Liesching, 2015;Marini et al, 2015). Also, most prototypes of nursing robot suggested nowadays are designed merely as assistants, not autonomous carers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure security of the elderly, it needs to implement real-time monitor to the home security. With rapid development of the computer technology, image processing technology, mobile Internet technology and robot technology, it is of great significance to develop a home security patrol robot [1] integrating monitoring, alarming, education, entertainment, and even assistance and home care of the elderly to improve the living quality and materialize the concept of the smart city.…”
Section: Introductionmentioning
confidence: 99%
“…4. Relations among various parts of the chassis control software system Of that, x, y and θ & are the translational velocity and the rotation angular velocity;1…”
mentioning
confidence: 99%